2010
DOI: 10.4269/ajtmh.2010.09-0514
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Distribution of Antimalarial Drug Resistance Alleles among Plasmodium falciparum Isolates from Gezira State, Central Sudan, and Gedarif State, Eastern Sudan

Abstract: In 2004, Sudan adopted artesunate + sulfadoxine/pyrimethamine (SP) combination as the first-line drug, in response to the high level of falciparum resistance to antimalarials. In 2007, a molecular study on antimalarial resistance linked genes, pfcrt, pfmdr1, pfdhfr, pfdhps, and pfATPase6, was conducted on 198 isolates from central and eastern Sudan. We observed a high frequency of point mutations at almost all loci analyzed, mainly of pfcrt 76T (72.7%), pfdhfr 51I (75.3%), and pfdhfr 108N (72.7%) alleles. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 53 publications
(49 reference statements)
5
21
1
Order By: Relevance
“…Many of the haplotypes detected in this study have been reported previously in Africa [28], [29]. Although the most dramatic increase was noted in the septuple mutant, T 76 Y 86 I 51 R 59 N 108 G 437 E 540 , from baseline to the year 5 survey, there was also a substantial increase in isolates containing the pfmdr1-86 sensitive sextuple mutant, T 76 N 86 I 51 R 59 N 108 G 437 E 540 .…”
Section: Discussionsupporting
confidence: 75%
“…Many of the haplotypes detected in this study have been reported previously in Africa [28], [29]. Although the most dramatic increase was noted in the septuple mutant, T 76 Y 86 I 51 R 59 N 108 G 437 E 540 , from baseline to the year 5 survey, there was also a substantial increase in isolates containing the pfmdr1-86 sensitive sextuple mutant, T 76 N 86 I 51 R 59 N 108 G 437 E 540 .…”
Section: Discussionsupporting
confidence: 75%
“…falciparum population in eastern Sudan carrying the mutant pfcrt allele CVIET [7]. Lower drug pressure is reflected by more wild type pfcrt where transmission is higher and perennial in central Sudan [53]. Moreover SP has been used intensively in patients where CQ failed.…”
Section: Discussionmentioning
confidence: 99%
“…Different mutations of Pfcrt indicating resistance have been reported in this study with total of 25.8%. However, this percentage is low compared to other areas in the country where Pfcrt mutations ranging from 63 to 100% were reported [7,11,16,30,31]. Chloroquine resistance mutations is not reversible.…”
Section: Discussionmentioning
confidence: 77%
“…Chloroquine resistance emerged worldwide as early as late fifties in Southeast Asia and South America [5]. In Sudan, chloroquine resistance started in late 1970s, and treatment failure became alarmingly high until the introduction of ACT in 2005 [4,6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation